An Introduction to Economic Analysis of Pest Management: Concepts of Partial Budgeting Analysis : FE1157, 9/2024 - Cai, Yetian; Li, Yi; Weng, Weizhe; Guan, Zhengfei (EDIS, 2024)
Pests have long posed a serious challenge in agricultural ecosystems, inflicting substantial economic losses on a global scale. In agricultural production, pests are often associated with crop yield losses, leading to a reduction in farm profits. This initial publication in the An Introduction to Economic Analysis of Pest Management series aims to educate agricultural producers, Extension agents, and researchers in other disciplines about partial budgeting analysis. Partial budgeting analysis is a fundamental tool widely used to analyze the economic viability of adopting various pest-management strategies.